KOMUNIKASI KEPIMPINAN BERKESAN: Effective Communication for Leaders - Akhtar, Helmi; Abdul Ghani Azmi, Ilhaamie (Jurnal Syariah, 2017)
Effective communication is essential for every leader. This is due to good communication can result in peace and harmony among followers or workers and is important for achieving objectives. Thus, this article focuses on effective leadership communication. A qualitative method was used whereby documents were examined for a clear understading of an Islamic form communication, the types of communication, and the principles and ethics behind said communication. Accordingly, this article will cover the definition and characteristics of effective communication from the Islamic perspective. Generally, this paper is different from previous articles in terms of its reliance on the thoughts of Imām al-Ghazalī regading the characterisctics of effective communication that should be practiced by leaders in the contemporary period.